Heroism and Imperialism in the Arctic: Edwin Landseer’s Man Proposes – God Disposes - Høvik, Ingeborg (Nordlit, 2008)
Edwin Landseer contributed the painting Man Proposes - God Disposes (Royal Holloway College, Egham), showing two polar bears amongst the remnants of a failed Arctic expedition, to the Royal Academy's annual exhibition of 1864. As contemporary nineteenth-century reviews of this exhibition show, the British public commonly associated Landseer's painting with the lost Arctic expedition of sir John Franklin, who had set out to find the Northwest Passage in 1845. Despite Landseer's gloomy representation of a present-day human disaster and, in effect, of British exploration in the Arctic, the painting became a public success upon its first showing. I will argue that a major reason why the painting became a success, was because Landseer's version of the Franklin expedition's fate offered a closure to the whole Franklin tragedy that corresponded to British nineteenth-century views on heroism and British-ness.